Survival after inpatient or outpatient pulmonary rehabilitation in patients with fibrotic interstitial lung disease: a multicentre retrospective cohort study. Issue 6 (30th August 2021) - Guler, Sabina Anna; Hur, Seo Am; Stickland, Michael K; Brun, Patrick; Bovet, Luc; Holland, Anne E; Bondarenko, Janet; Hambly, Nathan; Wald, Joshua; Makhdami, Nima; Kreuter, Michael; Gloeckl, Rainer; et al.
Abstract : Background: The impact of pulmonary rehabilitation (PR) on survival in patients with fibrotic interstitial lung disease (ILD) is unknown. Given the challenges conducting a large randomised controlled trial, we aimed to determine whether improvement in 6-minute walk distance (6MWD) was associated with better survival. Methods: This retrospective, international cohort study included patients with fibrotic ILD participating in either inpatient or outpatient PR at 12 sites in 5 countries. Multivariable models were used to estimate the association between change in 6MWD and time to death or lung transplantation accounting for clustering by centre and other confounders. Results: 701 participants (445 men and 256 women) with fibrotic ILD were included. The mean±SD ages of the 196 inpatients and 505 outpatients were 70±11 and 69±12 years, respectively. Baseline/changes in 6MWD were 262±128/55±83 m for inpatients and 358±125/34±65 m for outpatients. Improvement in 6MWD during PR was associated with lower hazard rates for death or lung transplant on adjusted analysis for both inpatient (HR per 10 m 0.94, 95% CI 0.91 to 0.97, p<0.001) and outpatient PR (HR 0.97, 95% CI 0.95 to 1.00, p=0.042). Participation in ≥80% of planned outpatient PR sessions was associated with a 33% lower risk of death (95% CI 0.49% to 0.92%). Conclusions: Patients with fibrotic ILD who improved physical performance during PR had better survival compared with those who did not improve performance. Confirmation of these hypothesis-generating findings in a randomised controlled trial would be required to definitely change clinical practice, and would further support efforts to improve availability of PR for patients with fibrotic ILD.